Risk Attitudes, Social Interactions, and the Willingness to Pay for Genotyping in Dairy Production. (16th November 2016) - Hailu, Getu; Cao, Ying; Yu, Xi
Abstract : Bovine Mastitis is one of the most prevalent and costly production diseases in the dairy industry in Canada and worldwide causing major animal welfare problems, environmental problems, and productivity losses. In this paper, we examine the effects of risk attitudes and social interactions on the willingness to pay (WTP) for genotyping animals for susceptibility to a chronic mastitis trait. We use contingent valuation with double bounded dichotomous choice questions to elicit producers' WTP. The estimated mean WTP for genotyping is approximately 50 per animal. Compared to the current market prices of commercially available comprehensive genotyping services, this estimate suggests a significant market potential for genotyping to be bundled with economically important disease traits. We also find evidence that both risk attitudes and social interactions have strong effects on the WTP for genotyping. Farmers with higher risk tolerance are willing to pay more for genotyping service. For dairy farmers with more concern about mastitis, risk tolerance has no significant effect on the WTP, while social interactions have a significant effect on the WTP. We also find a strong interaction effect between risk tolerance and social interactions. The findings encourage interest in questions about how risk attitudes, social networks, and their interactions shape the adoption of and the WTP for a novel agricultural technology. La mastite bovine est la maladie de production la plus répandue et la plus coûteuse de l'industrie laitière au Canada et mondialement causant des problèmes en ce qui concerne le bien‐être des animaux, l'environnement et la perte de productivité. Cet article examine les effets de l'attitude à l′égard du risque et des interactions sociales concernant la volonté de payer pour le génotypage d'animaux pour le dépistage de la susceptibilité à posséder le trait de mastite chronique. L'évaluation contingente avec questions à double proposition dichotomique a été utilisée afin d'obtenir la volonté de payer des producteurs. La volonté moyenne estimée de payer pour le génotypage s'élève à approximativement 50 par animal. Comparée aux prix courants du marché pour les services commerciaux complets de génotypage, cette estimation suggère un potentiel commercial significatif pour grouper le génotypage à d'autres traits de maladie d'importance économique. Nous trouvons aussi trouvé que les attitudes à l′égard du risque et les interactions sociales avaient un impact significatif sur la volonté de payer pour le génotypage. Les fermiers démontrant une grande tolérance au risque sont disposés à payer plus pour les services de génotypage. Pour les producteurs laitiers préoccupés par la mastite, la tolérance vis‐à‐vis du risque n'a aucun effet sur la volonté de payer, tandis que les interactions sociales en ont une importante. Nous notons aussi un effet significatif d'interaction entre la tolérance pour le risque et les interactions sociales. Les résultats favorisent un questionnement au sujet des attitudes à l′égard du risque, des réseaux sociaux et de leurs interactions, cherchant comment ces derniers guideront l'adoption de nouvelles technologies agricoles et la volonté d'en acquérir.